2022
DOI: 10.2147/idr.s387292
|View full text |Cite
|
Sign up to set email alerts
|

Practices, Knowledge, and Attitudes of Chinese University Students Toward Traditional Chinese Herbal Medicine for the Control of COVID-19

Abstract: Background The application of traditional Chinese herbal medicine has been officially recommended and strongly promoted in China as an important complement to conventional prevention and treatment for COVID-19. Capturing the practices, knowledge and attitudes of young adult population toward using Chinese herbs for COVID-19 is important for understanding the future of Chinese herbal medicine over the coming decades. Methods This cross-sectional questionnaire-based study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…Despite the fact that the overall average environmental knowledge levels regarding disinfectants were extremely low (2.12–2.42 out of a total of 5), participants having good practice of consuming environmental friendly disinfectants achieved significantly higher environmental knowledge scores. This finding was in accordance with the Information-Motivation-Behavioral Skills (IMB) model proposing that the awareness and understanding are generally prerequisite to willingness and behavioral change ( 29 , 30 ). The poor environmental knowledge about disinfectants was also corroborated by the assessment results of practice showing a considerable proportion of participants had no opinion about the environmental aspect of disinfectant products and did not clearly know the active disinfectant ingredients for household use.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fact that the overall average environmental knowledge levels regarding disinfectants were extremely low (2.12–2.42 out of a total of 5), participants having good practice of consuming environmental friendly disinfectants achieved significantly higher environmental knowledge scores. This finding was in accordance with the Information-Motivation-Behavioral Skills (IMB) model proposing that the awareness and understanding are generally prerequisite to willingness and behavioral change ( 29 , 30 ). The poor environmental knowledge about disinfectants was also corroborated by the assessment results of practice showing a considerable proportion of participants had no opinion about the environmental aspect of disinfectant products and did not clearly know the active disinfectant ingredients for household use.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have shown that age, gender, and education level are all predictors of TCM use: older age, lower education level, and women are more likely to choose TCM. 6 , 15 , 22 In addition, relevant studies have shown that risk perception is related to TCM attitudes. The health belief model suggests that, in general, the greater the public’s perceived susceptibility and severity to disease, the more inclined they are to adopt healthy behaviors.…”
Section: Theoretical Reasoning and Hypothesismentioning
confidence: 99%
“…12 Relevant studies on the Chinese public's attitude toward TCM prevention and treatment of COVID-19 in recent years show that the Chinese public has a positive attitude toward using TCM for epidemic prevention, even though its effectiveness remains controversial. [13][14][15][16][17][18] A study on the debate among Chinese netizens about the effectiveness of TCM found that the current debate among Chinese Internet users about the effectiveness of TCM in treating COVID-19 did not change their overall positive attitude towards TCM, which was influenced by nationalist sentiments. 8 Research has found that in the absence of specific drugs for COVID-19, more than half of the participants agreed that TCM could be used to prevent and treat COVID-19, and most participants were willing to take TCM to prevent COVID-19 but were unsure of its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Previous research showed that compared with non-medical students, medical students were more worried about the unclear pharmacological and toxicological properties of Chinese herbs. 19 However, another study showed that people with a medical education background were more supportive of TCM than others, with only 1% holding a negative attitude. 26 Therefore, whether people in the medical profession were more or less likely to support TCM treatment of COVID-19 is still a controversial topic that is worth further investigation, so we raise our RQ3:…”
Section: Introductionmentioning
confidence: 98%
“… 18 A study on college students using TCM to treat COVID-19 showed that 82% of the 313 participants held a supportive attitude, 16% held a neutral attitude and 2.4% held a negative attitude. 19 …”
Section: Introductionmentioning
confidence: 99%